Canadian Labour – The Need for Social Renewal - Carew, Anthony (Relations industrielles / Industrial Relations, 1968)
It is now necessary that the labour movement free itself from a short-sighted interest in ad-hoc gains and start to take into account, with far more rigour than before, the wider, social and economic spectrum.